The importance of atmospherics in the choice of hyper and supermarkets - Marques, S. H. (2016)
Are the atmospheric variables equally relevant for supermarket and hypermarket customers? As a contribution to the customers’ choice of the store format, firstly this work aims to determine the perception of differences between hypermarkets and supermarkets in terms of store attributes. Second, it sheds light on the role played by atmospherics in the customers’ decision process. This study uses a logit approach to model the probabilistic choice of the customers’ store format using atmospheric and other marketing variables as important attributes of the grocery store. The model’s estimation is based on personal interviews conducted during the shopping process in urban supermarkets and hypermarkets belonging to the same retail chain. The findings show that although the atmospheric variables are significantly important for both store formats, the customers perceive differently the importance of each retail atmospheric cue and other marketing variables, when buying in a hypermarket or in a supermarket: the choice of buying in hypermarket is explained by the significant importance given to the latent variables named pleasant atmosphere and accessibility and responsiveness; in contrast, the choice of buying in supermarkets is explained by the significant importance given to the latent variable nice decoration and empathy with the staff. The other latent variable designated by other marketing variables is only significantly important in the decision of choosing supermarkets.